Induction of angiogenesis via topical delivery of basic‐fibroblast growth factor from polyvinyl alcohol–dextran blend hydrogel in an ovine model of acute myocardial infarction. (4th June 2012) - Fathi, Ezzatollah; Nassiri, Seyed Mahdi; Atyabi, Nahid; Ahmadi, Seyed Hossein; Imani, Mohammad; Farahzadi, Raheleh; Rabbani, Shahram; Akhlaghpour, Shahram; Sahebjam, Mohammad; Taheri, Mohammad
Abstract Hydrogels are currently used as interesting constructs for the delivery of proteins. In this study, a novel polyvinyl alcohol–dextran (PVA–Dex) blend hydrogel was used for controlled delivery of basic‐fibroblast growth factor (bFGF). These biocompatible constructs were sutured to the epicardium as patches on the heart surface to provide slow release of bFGF to the infarcted site in an ovine model of myocardial infarction (MI). Eighteen sheep were randomly divided into three groups (n = 6 each), including group I (control without any patch and bFGF), group II (patch without bFGF) and group III (patch incorporating 100 µg bFGF). They were subjected to coronary artery ligation after lateral thoracotomy, and then in groups II and III the patches were implanted 20–30 min after MI. Cardiac function was assessed by both echocardiography and magnetic resonance imaging (MRI) 2 months after implantation. Then the animals were sacrificed and the hearts subjected to histopathological examination, immunohistochemistry and electron microscopy. Heart lysates were subject to protein expression analysis through western blotting. The results showed that sustained release of bFGF using PVA–Dex blend hydrogel strongly stimulated angiogenesis and increased wall thickness index in the infarcted myocardium. The patch also significantly attenuated the increase in left ventricular end‐systolic diameter, but it did not improve cardiac function within 2 months of myocardial infarction. In conclusion, PVA–Dex gel incorporating bFGF can be used as a sustained release construct for therapeutic angiogenesis in ischaemic heart disease. Copyright © 2012 John Wiley & Sons, Ltd.